2021
DOI: 10.3390/jcs5080207
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of h-MoO3 Nanorods and the Properties of the MoO3/WEP Composite Coatings Research

Abstract: In this study, we prepared a novel coating composed of hexagonal molybdenum oxide (h-MoO3) nanofiller and waterborne epoxy resin (WEP) to provide corrosion protection. We optimized the h-MoO3 nanorod synthesis methodology first by changing different parameters (pH, temperature, etc.). Furthermore, the as-prepared h-MoO3 rods were characterized using a scanning electron microscope (SEM) and X-ray diffraction (XRD). Finally, the electrochemical impedance spectroscopy (EIS) test results verified that the anticorr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The crystal orientations of MoO 3 are (022), (513), (800), and (424), corresponding to orthorhombic crystal α‐MoO 3 . [ 27 ] Figure 1e shows XRD patterns of the CsPbBr 3 /MoO 3 heterojunctions on SiO 2 /Si substrates. It can be observed that the diffraction peaks of both CsPbBr 3 perovskite and MoO 3 are reflected.…”
Section: Resultsmentioning
confidence: 99%
“…The crystal orientations of MoO 3 are (022), (513), (800), and (424), corresponding to orthorhombic crystal α‐MoO 3 . [ 27 ] Figure 1e shows XRD patterns of the CsPbBr 3 /MoO 3 heterojunctions on SiO 2 /Si substrates. It can be observed that the diffraction peaks of both CsPbBr 3 perovskite and MoO 3 are reflected.…”
Section: Resultsmentioning
confidence: 99%
“…Shokri‐Oojghaz et al [ 107 ] characterized the effects of relative volume of CNT, aggregation, CNT distribution, geometry and loading on the mechanical properties of the nanocomposite sandwich cylinders and found that, in order to improve the mechanical properties of composites, it is beneficial to improve distribution of CNT compared to adding CNT content in the nanocomposites. Zhou et al [ 108 ] developed a theoretical model to study flexural properties of functionally graded nanocomposites. Further, they proved that width‐to‐thickness ratio, plate's aspect ratio and, relative volume and distribution pattern of CNTs significantly affects nonlinear flexural properties of composite structures.…”
Section: Literature Reviewmentioning
confidence: 99%